Drivers of Bank Profitability: A Study of ROA Determinants at the Yogyakarta Regional Development Bank - Bambang Jatmiko (KENDALI: Economics and Social Humanities, 2025)
This study aims to examine the impact of operational efficiency (BOPO), net interest margin (NIM), non-performing loans (NPL), statutory reserve requirements (GWM), and capital adequacy ratio (KPMM) on return on assets (ROA) at the Regional Development Bank of the Special Region of Yogyakarta. The analysis is based on monthly data spanning from January 2017 to December 2024. A multiple linear regression model is employed to assess the relationship between the selected financial ratios and ROA. The empirical findings reveal that BOPO, GWM, and KPMM have a statistically significant negative effect on ROA, while NIM exerts a positive influence. Conversely, NPL is found to have no significant effect on ROA. The results suggest that bank management should prioritize enhancing operational efficiency and capital structure, while also optimizing interest margin policies, to improve overall profitability.